Sektor Industri Pariwisata Dengan Media Digital Di Masa Pandemi Covid-19 - Luh Suryatni (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
Since the pandemic caused by the SARS-CoV-2 virus (COVID-19) appeared in the end of 2019 it significantly affected the tourism industry. Government in Indonesia have adopted emergency measures and restrictions that have affected the mobility of everyone. From museum to amusement park, they were empty, even closed since people’s movements were stopped, and travel among different territories was strictly controlled. Lockdown and quarantine around the world caused by COVID-19 has harmed people’s livelihoods and the world economy. During this situation government pushing the idea of the advantage of digital era and adopted by tourism industry. The purpose of this paper is to find out and analyzing tourism industry has facing during the pandemic and how it used digital technology in purpose of revive their condition. The data collection method used is a literature study with descriptive analysis techniques. The results are showed that Indonesia tourism industry starting to get better in situation by using digital media and working together with application that provides help for tourist planning the trip and open the new chances of new business.